Translational Medicine in Alzheimer's Disease: The Journey of Donanemab From Discovery to Clinical Application - Nandhini Jayaprakash; Karthikeyan Elumalai (Chronic Diseases and Translational Medicine)
ABSTRACT Substantial research has been conducted to identify an efficient treatment for Alzheimer's disease (AD). Existing treatments, including cholinesterase inhibitors and N‐methyl D‐aspartate (NMDA) receptor antagonists, do not reverse or slow the disease course but only treat its manifestations. This limitation has brought attention to the need for treatments that modify the amyloid‐beta (Aβ) and tau pathology of the disease. One recent advancement in AD treatment is donanemab, a monoclonal antibody intended to clear Aβ plaques in the brain. It targets pyroglutamyl(3)‐Aβ protein (3–42) to remove Aβ deposits and alter the disease course. This review explores the timeline of donanemab use from discovery to clinical use. The pharmacodynamics and pharmacokinetics of the drug are discussed along with typical and suboptimal preclinical and clinical trial results in terms of efficacy, safety, and tolerability. Thus, donanemab is more effective than donepezil and rivastigmine in removing plaques and improving cognition. At the same time, it is not devoid of safety concerns that are typical of the majority of amyloid‐targeted medicines. The control to end the treatment after plaque cleaning is a unique selling point for some patients, making it more attractive. The innovation and development of donanemab from research to clinical practice are a clear representation of the role of the field of translational medicine in the practical application of new knowledge in the treatment of AD.